Suicidal Thoughts and Behaviors in Children of Immigrants: The Experience of Korean-American Women. Issue 2 (3rd April 2019) - Chung, Saras; Lesorogol, Carolyn
ABSTRACT: This qualitative study examines the experience of Korean-American women who had suicidal thoughts and/or used nonsuicidal self-injury (NSSI) during adolescence. This study aims to understand the etiology, help-seeking behaviors, and recovery of these young women. Eleven Korean-American women (mean age 26.7) were recruited and interviewed using in-depth semi-structured interviews. Transcripts were coded using a grounded theoretical framework. Themes indicate that participants experienced poor relationships with a parent, an inability to process their difficulties, and academic success despite their behaviors. Participants also indicated feelings of perfectionism and did not seek help, resulting in a theme called the paradox of perfection.